The long Earth - Pratchett, Terry; Baxter, Stephen (New York : Harper, 2012)
The stepper enables a person using it to step sideways into another America, another wherever that person happened to be, another Earth. And if the person using it keeps on stepping, they keep on entering even more Earths. This is the Long Earth. And the further away a stepper travels, the stranger -- and sometimes more dangerous -- the Earths become.
Keywords: Space and time -- Fiction; Science fiction